Identification of alkaline pH optimum of human glucokinase because of ATP-mediated bias correction in outcomes of enzyme assays - Šimčíková, Daniela; Heneberg, Petr (Scientific reports, 2019)
Adenosine triphosphate (ATP) is a crucial substrate and energy source commonly used in enzyme reactions. However, we demonstrated that the addition of this acidic compound to enzyme assay buffers can serve as a source of unnoticed pH changes. Even relatively low concentrations of ATP (up to 5 mM) shifted pH of reaction mixtures to acidic values. For example, Tris buffer lost buffering capacity at pH 7.46 by adding ATP at a concentration higher than 2 mM. In addition to the buffering capacity, the pH shifts differed with respect to the buffer concentration. High ATP concentrations are commonly used in hexokinase assays. We demonstrated how the presence of ATP affects pH of widely used enzyme assay buffers and inversely affected KM of human hexokinase 2 and S0.5 of human glucokinase. The pH optimum of human glucokinase was never reported before. We found that previously reported optimum of mammalian glucokinase was incorrect, affected by the ATP-induced pH shifts. The pH optimum of human glucokinase is at pH 8.5-8.7. Suggested is the full disclosure of reaction conditions, including the measurement of pH of the whole reaction mixtures instead of measuring pH prior to the addition of all the components.
Keywords: hexokinasa; Proof of Concept Study; koncentrace vodíkových iontů; Recombinant Proteins; rekombinantní proteiny; adenosintrifosfát; Adenosine Triphosphate; substrátová specifita; Hydrogen-Ion Concentration; enzymatické testy; Enzyme Assays; ověření koncepční studie; Substrate Specificity; Hexokinase